1987
DOI: 10.1080/0028825x.1987.10410078
|View full text |Cite
|
Sign up to set email alerts
|

The roles of lizards in New Zealand plant reproductive strategies

Abstract: Geckos in the genus Hoplodactylus regularly visit flowers to feed on nectar. They collect considerable amounts of pollen, mostly on their throats, from species such as Metrosideros excelsa and Phormium tenax. This pollen can be carried for many metres and for up to at least 12 hours, and there is thus the opportunity for lizards to transfer it to a conspecific plant to effect crosspollination.Geckos in the genus Hoplodactylus and skinks in the genera Leiolopisma and Cyclodina all include considerable quantitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
130
0
5

Year Published

1990
1990
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(137 citation statements)
references
References 19 publications
2
130
0
5
Order By: Relevance
“…Whitaker (1968) recorded 73 m as the maximum distance movement by Hoplodactylus duvaucelli (Gekkonidae) in New Zealand. This author also found dispersed seeds 12 m away from the nearest fruiting plants (Whitaker, 1987). Barquín and Wildpret (1975) cited up to 50 m for seeds of Plocama pendula (Rubiaceae) being dispersed by Gallotia galloti from the nearest potential parent plant.…”
Section: Lizards As Seed Dispersers?mentioning
confidence: 97%
See 1 more Smart Citation
“…Whitaker (1968) recorded 73 m as the maximum distance movement by Hoplodactylus duvaucelli (Gekkonidae) in New Zealand. This author also found dispersed seeds 12 m away from the nearest fruiting plants (Whitaker, 1987). Barquín and Wildpret (1975) cited up to 50 m for seeds of Plocama pendula (Rubiaceae) being dispersed by Gallotia galloti from the nearest potential parent plant.…”
Section: Lizards As Seed Dispersers?mentioning
confidence: 97%
“…Klein, 1977;Janzen, 1982;Iverson, 1985;Traveset, 1990;Hartley et al, 2000) and the omnivorous ones (e.g. Whitaker, 1987;Fialho, 1990;Valido and Nogales, 1994;Willson et al, 1996;Lord and Marshall, 2001;Olesen and Valido, 2003;Rodríguez-Pérez et al, 2005).…”
mentioning
confidence: 99%
“…The inflorescences are set on the periphery of the canopy and bear hermaphrodite, large, red brush flowers that produce copious nectar. Flower visitors include the native New Zealand honeyeaters (Meliphagidae) (Angehr 1986), a range of introduced birds (Anderson 1997), native and introduced bees (Donovan 1980;Salmon 1980), and also geckos and bats (Whitaker 1987;Eifler 1995;Arkins 1996). Seed production in pohutukawa is reported to be generally low, and the majority of the seeds are sterile (Dawson 1968(Dawson , 1970a.…”
Section: Introductionmentioning
confidence: 99%
“…In this study we compare UV reflectance of fruits of 41 indigenous species having a range of perceived fruit colours, life-forms, and taxonomic affiliations. Most of the species are dispersed by birds, although Whitaker (1987) has suggested that small lizards are primary dispersers of many white or translucent fruits flecked with pale blue or pale pink. Small-leaved Coprosma species at low altitudes characteristically have nonred fruit colours which may also be preferred by nectarivorous birds (Lee et al 1988).…”
Section: Introductionmentioning
confidence: 99%
“…28 1980), have UV VISIOn. Melicytus alpinus* (Violaceae) was included in this study as Whitaker (1987) considers it to be dispersed primarily by small lizards, although there is no evidence that these animals can detect UV.…”
Section: Introductionmentioning
confidence: 99%